2015
DOI: 10.1186/s13023-015-0304-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with locked-in syndrome: Evolution over a 6-year period

Abstract: BackgroundImproved knowledge of the quality of life (QoL) of locked-in syndrome (LIS) patients have implications for managing their care, and assists clinicians in choosing the most appropriate interventions. We performed a survey of a population of LIS patients to describe the course of the QoL of LIS patients over a 6-year period and to determine the potential predictive factors of QoL changes over time.MethodThis is a study performed over a 6-year period in patients with a LIS diagnosis. Questionnaires were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 41 publications
5
67
1
2
Order By: Relevance
“…It has been previously observed that patients' subjective QoL is not related to physical impairments; this observation agrees with previous studies of different motor neuron disorders (1,2,25,34,38,48-53), SCI patients (54), and LIS patients (5,9,49,53,55). This illustrates the "disability paradox" reported by Albrecht and Devlieger (51,56).…”
Section: Assistance To Interpret Quality Of Life Scoressupporting
confidence: 91%
See 2 more Smart Citations
“…It has been previously observed that patients' subjective QoL is not related to physical impairments; this observation agrees with previous studies of different motor neuron disorders (1,2,25,34,38,48-53), SCI patients (54), and LIS patients (5,9,49,53,55). This illustrates the "disability paradox" reported by Albrecht and Devlieger (51,56).…”
Section: Assistance To Interpret Quality Of Life Scoressupporting
confidence: 91%
“…The QoL of people in heavy motor disabilities is often subject to representations of caregivers whose patients depend: healthy individuals, caregivers, family support and health professionals frequently underestimate the QoL of the patients assuming that QoL in severely handicapped people is very poor (4)(5)(6)(7). But some studies showed that these persons may report relatively satisfactory QoL levels that are stable over time (8,9). The QoL is sometimes better than patients presented other disabilities, such as patients with new diagnoses of Alzheimer's disease (10) and patients with facial prostheses (11).…”
Section: The Major Interest Of Patient's Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…Locked-in patients typically have little to no voluntary muscle control but retain cognition and awareness [29][30][31][32][33]. Although methods exist to provide basic communicative capabilities to locked-in patients [33][34][35][36] and are associated with increases in patient-reported quality of life [31,32], these approaches often involve tedious and difficult to learn procedures such as selecting characters one at a time at rates less than ten characters per minute (typing rates are typically more than 175 characters per minute in healthy individuals). Development of a device capable of directly interpreting intended speech from neural activity could result in significant improvements to the speed and naturalness of assistive speech technology and, as a result, the quality of life for impaired patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Mortality in the first 4 months reaches 87% in vascular cases, but may be reduced if the diagnosis and rehabilitation are initiated precociously. 1,7 After clinical stabilization, survival may reach 83% in 10 years and 40% in 20 years. 1,7 The clinical picture should increase suspicion of LIS when the patient presents with quadriplegia and anarthria with preserved consciousness and cognition, [1][2][3][4][5][6] although ophthalmoplegia and reduced consciousness can be found during the acute phase of the injury.…”
Section: Discussionmentioning
confidence: 99%